Oral Eplerenone Versus Observation in the Management of Acute Central Serous Chorioretinopathy: A Prospective, Randomized Comparative Study - Ramesh Venkatesh; Arpitha Pereira; Chaitra Jayadev; Vishma Prabhu; Aditya Aseem; Kushagra Jain; Bharathi Bavaharan; Naresh Kumar Yadav; Jay Chhablani (MDPI AG, 2020)
In this prospective, interventional case-control study, 58 patients with unilateral acute central serous chorioretinopathy (CSCR) were recruited. Patients ≥ 18 years age, presenting with first episodes of acute CSCR, were included. Acute CSCR was defined by the presence of subretinal fluid (SRF) and symptoms for <12 weeks duration with no clinical or imaging features of chronicity. Patients were alternately divided into treatment (Table Eplerenone 50 mg/day for minimum 1 month) and observation groups. Vision, SRF height and subfoveal choroidal thickness (SFCT) were checked at 1-, 2- and 3-months in both eyes of each group. Each group had 29 eyes. Mean age was 40.4 ± 7.1 and 43.3 ± 8.34 years in treatment and observation group, respectively. Mean symptom duration was 6.46 ± 1.45 and 5.87 ± 2.09 weeks, respectively. Vision improvement to 6/6 was seen in 92%, 100% and 100% cases in treatment group and 74%, 86% and 100% in control group at each visit, respectively. Complete SRF resolution in the treatment group was noted in 45%, 55% and 62% cases at each respective monthly visit. In the observation group, complete SRF resolution was noted in 10%, 21% and 31% at 1-, 2- and 3-month visits, respectively. SRF (p < 0.001) and SFCT (p < 0.001) reduction was noted in the affected eye of both groups. SFCT was reduced in the fellow eye after treatment (p = 0.005) compared to the observation group (p = 0.276). In conclusion, oral eplerenone achieves faster SRF resolution and vision improvement in acute CSCR. Additionally, it shows beneficial effects on the fellow eye.